SERS-based detection of DNA methylation for cancer diagnosis: Cation-mediated adsorption to silver nanoparticles - Stefania D. Iancu; Vlad Moisoiu; Bogdan Adrian Tigu; Andrei Stefancu; Oana M. Biro; Ciprian Tomuleasa; Nicolae Leopold (PLoS ONE, 2025)
The high-throughput analysis of DNA methylation markers by label-free surface-enhanced Raman scattering (SERS) holds significant promise for advancing cancer detection. However, a deeper understanding of the factors governing DNA adsorption onto metal surfaces and the identification of reliable SERS bands indicative of DNA methylation levels are still needed. In this study, we evaluated the effects of several cations (Ca2+, Mg2+, Al3+, Be2+, Zn2+, Cu2+, Fe2+, and Na⁺) on the SERS signal of DNA and identified Ca2+ as providing the highest enhancement. Thus, the addition of 5x10-4 M Ca2+ yielded optimal SERS signals for genomic DNA extracted from calf thymus and from six human cell lines, including both benign and malignant types with varying methylation levels. Notably, the SERS activation effect due to Ca2+ could also be replicated by lowering the pH, suggesting that Ca2+ increases the signal enhancement by generating surface Ag⁺ which favors the adsorption of DNA. A strong positive correlation (R = 0.94, p = 0.005) was observed between the intensity of the SERS band at 790 cm-1 and the level of 5-methylcytosine, establishing this band as a robust marker for DNA methylation. This finding was further validated by monitoring methylation levels in a 180 bp DNA sequence from the promoter region of the SEPT9 gene, an FDA-approved biomarker for colorectal cancer. Additionally, the use of SYBR Green fluorescence assays revealed that hypermethylated genomic DNA exhibits greater affinity for silver surfaces compared to lower methylated DNA. Collectively, these findings provide important theoretical insights and practical directions for the development of future nanoparticle-based cancer detection assays utilizing methylation markers.